2022
DOI: 10.17977/um057v12i2p90-98
|View full text |Cite
|
Sign up to set email alerts
|

Profil Indeks Massa Tubuh Atlet Cabang Bela Diri Komite Olahraga Nasional Indonesia Kota Makassar

Abstract: IMT (Indeks Massa Tubuh) adalah metode untuk mengetahui dan menilai status gizi dengan cara pengambilan nilai berat badan dan tinggi badan seseorang. Untuk mengetahui kondisi atlet secara optimal yaitu dengan salah satu cara mengukur indeks massa tubuh sebelum melakukan kompetisi pada pekan olahraga provinsi Sulawesi Selatan di kabupaten Sinjai. Tujuan dari penelitian adalah untuk mengetahui indeks massa tubuh atlet cabang bela diri KONI kota Makassar. Sampel dalam penelitian adalah atlet cabang olahraga belad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
0
0
3
Order By: Relevance
“…BMI can be an indicator or describe adipocyte levels in a person's body (Wibowo & Hakim, 2019). This is in line with research conducted by (Haeril et al, 2022) which revealed that BMI (Body Mass Index) is a method for knowing and assessing nutritional status by taking a person's weight and height values. Ideal body weight and height conditions can affect performance in a match, this statement is in accordance with the opinion that in playing football, with ideal body weight athletes can make movements in football well as a whole (Gumantan & Mahfud, 2020).…”
Section: Resultssupporting
confidence: 89%
“…BMI can be an indicator or describe adipocyte levels in a person's body (Wibowo & Hakim, 2019). This is in line with research conducted by (Haeril et al, 2022) which revealed that BMI (Body Mass Index) is a method for knowing and assessing nutritional status by taking a person's weight and height values. Ideal body weight and height conditions can affect performance in a match, this statement is in accordance with the opinion that in playing football, with ideal body weight athletes can make movements in football well as a whole (Gumantan & Mahfud, 2020).…”
Section: Resultssupporting
confidence: 89%
“…Angka ini menunjukkan peningkatan dari tahun sebelumnya yang hanya sekitar 4.000 orang. Kenaikan jumlah atlet ini dipicu oleh berbagai faktor, termasuk peningkatan minat masyarakat terhadap olahraga tinju dan dukungan yang diberikan oleh pemerintah dan sektor swasta [29].…”
Section: Boxingunclassified
“…Selain nilai IMT, status gizi dapat diukur dengan menggunakan antropometri lingkar pinggang, hal ini dapat melihat distribusi lemak di bawah kulit pada atlet. Menurut peeliatian Haeril,et,al (2022) status gizi pada atlet beladiri memiliki nilai kategori berbeda-beda tergantung kategori atau kelas berat badan pada saat pertandingan. (14,15).…”
Section: Hasilunclassified
“…Menurut peeliatian Haeril,et,al (2022) status gizi pada atlet beladiri memiliki nilai kategori berbeda-beda tergantung kategori atau kelas berat badan pada saat pertandingan. (14,15).…”
Section: Hasilunclassified